Perhubungan warna dengan perasaan dalam sesebuah catan - Nor Shaida, Binti Che Hashim. (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study is one attempt to seek out the relationship between colour with feeling in a painting. The researcher is interested to discover the ability of colour in influencing as well as affecting one's feeling towards the content of an enclosed message.